Elaborated Cost Variation Study of Various Brands of Anti-Asthmatic Drugs Available in Indian Market - Gadhade, Jyoti B.; Magar, Yogesh B.; Hiray, Rajesh S.; Ghongane, Balasaheb B. (Technological Innovation in Pharmaceutical Research Vol. 8, 2021)
Objective: Asthma is a chronic inflammatory lung disease that affects people of all ages and is a major cause of morbidity and death across the world. It need ongoing medical attention. High and exorbitant prescription prices are one of the most common causes of non-compliance and treatment failure. The cost of pharmaceuticals has a significant impact on patient treatment, particularly in underdeveloped nations. It has been shown that the cost of different brands of the same generic medicine varies greatly. If doctors are unaware, they may prescribe expensive brands, which will result in non-adherence. The purpose of this study was to determine the cost differences between several anti-asthmatic medicine brands. Methods: From the newest edition of Drug Today 2017, the least and highest cost in Rupees (INR) of a certain anti-asthmatic agent made by several pharmaceutical firms in the same strength were listed. Each brand's cost ratio and percentage cost variance were recorded Results: The costs of anti-asthmatic medications varied significantly in this investigation. The highest percent cost variation was found for Doxophylline 400 mg (3100%), followed Deflazacort 6 mg (1300%), Methylprednisolone 4 mg (1104%), Combination of Formoterol and Budesonide (444%), Salbutamol 4 mg caps (363%), Theophylline and Salbutamol combination(236%), Ketotifen 1 mg (217%). Fluticasone 50 mcg (0.4%), Cromolyn 20 mg (2%), Formoterol 12 mcg (11.5%), Tiotropium 18 mcg (11.5%), Ipratropium 20 mcg/200 mdi (19%), and others were determined to have the lowest percent cost fluctuations. Conclusion: The government should look at the pricing control strategy for anti-asthmatic pharmaceuticals made by various Indian firms, so that the prices of different brands stay consistent, quality assured, and cheap. Doctors must prescribe logically, selecting cost-effective drugs depending on the health state of the country.